Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1/ 3(x - 2) = 9 => x - 2 = 3 => x = 5
2/ 3(x - 36) = 216 => x - 36 = 72 => x = 108
3/ (x - 3)3 = 33 => x - 3 = 3 => x = 6
4/ 2x = 32 => 2x = 25 => x = 5
5/ 3x - 16 = 2.74 : 73 = 14 => 3x = 30 => x = 10
6/ (6x - 39) : 3 = 201 => 6x - 39 = 603 => 6x = 642 => x = 107
7/ (3x - 15)2 = 81 => (3x - 15)2 = 92 => 3x - 15 = 9 => 3x = 24 => x = 8
8/ 3(x + 4) = 105 => x + 4 = 35 => x = 31
9/ 12x - 43 = 4.84 : 83 = 32 => 12x = 32 : 64 => 12x = 1/2 => x = 1/24
10/ 41 - (2x - 5) = 680 => 2x - 5 = -639 => 2x = -634 => x = - 317
\(a)3-\left(17-x\right)=-24+12\)
\(\Leftrightarrow3-17+x=-12\)
\(\Leftrightarrow-14+x=-12\)
\(\Leftrightarrow x=-12+14=2\)
a) 3 - (17 - x) = -24 + 12
=> 3 - 17 + x = -12
=> -14 + x = -12
=> x = -12 + 14
=> x = 2
b) -5 + (16 - x) = 22.3 - 52
=> -5 + 16 - x = 12 - 25
=> 11 - x = -13
=> x = 11 + 13
=> x = 24
c) -26 - (x - 7) = 34 - 92
=> -26 - x + 7 = 81 - 81
=> -19 - x = 0
=> x = -19 - 0
=> x = -19
d) -36 - (4 - x) = 37 + (-5)
=> -36 - 4 + x = 32
=> -40 + x = 32
=> x = 32 + 40
=> x = 72
1) x - 36 + 12 = - x+ 10
=> x + x = 10 + 24
=> 2x = 34
=> x = 34/2 = 17
2) (x + 15) - (11 - x) = (-2)2
=> x + 15 - 11 + x = 4
=> 2x = 4 - 4
=> 2x = 0
=> x = 0
3) 40 - 4x2 = (-6)2
=> 40 - 4x2 = 36
=> 4x2 = 40 - 36
=> 4x2 = 4
=> x2 = 1
=> x = \(\pm\)1
4) (-50) + 10x2 = (-25) x |-2|
=> -50 + 10x2 = -50
=> 10x2 = -50 + 50
=> 10x2 = 0
=> x2 = 0
=> x = 0
5) |x + 1| = 2020
=> \(\orbr{\begin{cases}x+1=2020\\x+1=-2020\end{cases}}\)
=> \(\orbr{\begin{cases}x=2019\\x=-2021\end{cases}}\)
6) (x + 1)5 + 8 = 0 (xem lại đề)
7) (-20) + x3 : 16 = -24
=> x3 : 16 = -24 + 20
=> x3 : 16 = -4
=> x3 = -4 . 16
=> x3 = -64 = (-4)3
=> x = -4
9) x14 = x17
=> x14 - x17 = 0
=> x14(1 - x3) = 0
=> \(\orbr{\begin{cases}x^{14}=0\\1-x^3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
10) (-36) + (1 - x)2 = 0
=> (1 - x)2 = 36
=> (1 - x)2 = 62
=> \(\orbr{\begin{cases}1-x=6\\1-x=-6\end{cases}}\)
=> \(\orbr{\begin{cases}x=-5\\x=7\end{cases}}\)
a) -152 - (3x + 1) = (-2).(-3)3
-152 - 3x - 1 = (-2).(-27)
-3x - 153 = 54
-3x = 54 + 153
-3x = 207
x = -69
b) x - 43 = (35 - x) - 48
x - 43 = 35 - x - 48
x - 43= -x - 13
x = -x - 13 + 43
x = 30 + x
x + x = 30
2x = 30
x = 15
7x-3.4=196
7x-3=49
x-3=2
x= -1
2x+3+2x=36
2x.9=36
2x=4
x=2
(52x.5x+2):25=1255
53x+2=517
x=5
36:[7.(x-3)+4]=2
7.(x-3)+4=36:2
7.(x-3)=18-4
x-3=14:7
x=2+3
x=5